Ethics: What is the Research Scenario in the Brazilian Symposium SBQS? - Carvalho, Luiz Paulo; Suzano, José Antonio; Anastassiu, Monica; Santoro, Flávia Maria; Oliveira, Jonice; Gonçalves, João Carlos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2021)
Many practitioners and researchers still consider software as program code, composed by algorithms and associated documentation, written in a programming language, and finally compiled or interpreted in a computational environment. The different facets of the software question, explored in interdisciplinary fields such as Digital Humanities, seem largely unexplored in Software Engineering and other traditional Computing fields of research. This paper aims to present an overview of ethical aspects through the publications of the Brazilian Symposium on Software Quality (SBQS). We followed a Systematic Literature Review (SLR) approach and presented quantitative and qualitative, and in-depth results, analyzing fifteen editions of the SBQS between 2006 and 2020. We adopted the concept of Ethics in a primary way, through searches for terms directly associated, and secondary, by terms such as Informed Consent, aligned with the definitions and concepts of Computational Ethics combined with episteme and good practices in Software Engineering. The results pointed to the minor occurrence of ethical aspects in SBQS publications, growing timidly over the years. We conclude that there is broad space to explore the theme of Computational Ethics combined with Software Quality.